Desenvolvimento tecnológico : a propriedade industrial na produção da guitarra elétrica e captadores no Brasil - Silva, Vinicius Nelson Lago (2016)
The knowledge society valorizes intangible assets. The creation of new products and functional improvement of these can promote competitive advantage and provide opportunities for economic development through IP Intellectual-Property. The Electric Guitar is an innovation that resulted from research and exploration carried by independent inventors. Production on a significant scale occurred from the 1940s in the United States, country that registered the first patents in the development of this musical instrument. Electric Guitar, which combines technological innovation since its inception, impacts the cultural development of Western society. It constitutes an important pillar for the industrial platform related to music that connects a worldwide chain of input suppliers and service providers. The pickup is the electromagnetic component that allowed the invention of the electric guitar in the United States of America and the Bahiana Guitar in Brazil. Both inventions are inducing cultural changes, however their economic impacts are different in scale and characteristics. The technological development of the pickups is crucial to the competitiveness of Electric Guitar's manufacturers. This dissertation represents an opportunity to reflect about the dynamic of this industry. Currently, the production of the Electric Guitar it is both industrial and artisanal. Brazil is a consumer market in expansion, what favors the increase of imports. In contrast, the international operations of brazilian industry in this sector is still under construction. Based on a descriptive applied research, the present dissertation is exploratory and explanatory. The elements of the research are: the current situation of the industrial segment of the Electric Guitar at the national level and in other relevant countries in the production and consumption of this instrument; exploration and analysis of the technological development of the pickup in Industrial Property databases, and the industry connection with the exportation incentive mechanisms. This dissertation aims to contribute to present this economic sector's potential and to demonstrate the importance of Industrial Property for its development, by considering the opportunities for the promotion of applied research, the Industrial Property registration, the development of technological innovation, and support mechanisms available in the National Innovation System.